2009
DOI: 10.1515/znc-2009-7-821
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Repair of Head and Neck Cancer Cells after Radio- and Chemotherapy

Abstract: DNA repair is critical for successful chemo- and radiotherapy of human tumours, because their genotoxic sensitivity may vary in different types of cancer cells. In this study we have compared DNA damage and the efficiency of its repair after genotoxic treatment with hydrogen peroxide, cisplatin and γ-radiation of head and neck squamous cell carcinoma (HNSCC). Lymphocytes and tissue cells from biopsies of 37 cancer patients and 35 healthy donors as well as the HTB-43 larynx cancer cell line were employed. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The study has found that radiotherapy for primary cancers was associated with an increased risk of developing second cancer in nearby organs. The development of second primary cancers in the irradiated head and neck area is biologically plausible with potential mechanisms such as DNA damage caused by radiotherapy 29 . An excess incidence of lung cancer was observed at 10 years after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The study has found that radiotherapy for primary cancers was associated with an increased risk of developing second cancer in nearby organs. The development of second primary cancers in the irradiated head and neck area is biologically plausible with potential mechanisms such as DNA damage caused by radiotherapy 29 . An excess incidence of lung cancer was observed at 10 years after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Conversely, it is reported in many studies that the response to anticancer therapy using DNA-reactive drugs may depend on DNA repair efficiency. [8][9][10][11][12][13][14][15][16][17][18][19][20] Therefore DNA repair efficiency may modulate the response of patients with breast cancer to adjuvant therapy. Adjuvant treatment for patients with breast cancer involves radiation therapy and a variety of chemotherapeutic agents, most frequently combinations of cyclophosphamide and anthracyclines.…”
Section: Introductionmentioning
confidence: 99%
“…DNA double chain damage repair is an essential mechanism of resistance of tumor cells to radiotherapy [31]. DNA damage can induce DNA damage response signaling (DDR signaling) in the tumor cells.…”
Section: Discussionmentioning
confidence: 99%